Recommendations for the delivery of therapeutic exercise for people with knee and/or hip osteoarthritis. An international consensus study from the OARSI Rehabilitation Discussion Group. Issue 3 (March 2023) - Holden, M.A.; Metcalf, B.; Lawford, B.J.; Hinman, R.S.; Boyd, M.; Button, K.; Collins, N.J.; Cottrell, E.; Henrotin, Y.; Larsen, J.B.; Master, H.; Skou, S.T.; et al.
Summary: Objective: To develop evidence-informed recommendations to support the delivery of best practice therapeutic exercise for people with knee and/or hip osteoarthritis (OA). Design: A multi-stage, evidence-informed, international multi-disciplinary consensus process that included: 1) a narrative literature review to synthesise existing evidence; 2) generation of evidence-informed proposition statements about delivery of exercise for people with knee and/or hip OA by an international multi-disciplinary expert panel, with statements refined and analysed thematically; 3) an e-Delphi survey with the expert panel to gain consensus on the most important statements; 4) a final round of statement refinement and thematic analysis to group remaining statements into domains. Results: The expert panel included 318 members (academics, health care professionals and exercise providers, patient representatives) from 43 countries. Final recommendations comprised 54 specific proposition statements across 11 broad domains: 1) use an evidence-based approach; 2) consider exercise in the context of living with OA and pain; 3) undertake a comprehensive baseline assessment with follow-up; 4) set goals; 5) consider the type of exercise; 6) consider the dose of exercise; 7) modify and progress exercise; 8) individualise exercise; 9) optimise the delivery of exercise; 10) focus on exercise adherence; and 11) provide education about OA and the role of exercise. Conclusion: The breadth of issues identified as important by the international diverse expert panel highlights that delivering therapeutic exercise for OA is multi-dimensional and complex.